Effect of Zilpaterol-HCl (Zilmax) on implanted and non-implanted feedlot steer performance and carcass characteristics - T.J. Baxa; J.P. Hutcheson; M.F. Miller; W.T. Nichols; M.N. Streeter; D.A. Yates; B.J. Johnson (Kansas Agricultural Experiment Station Research Reports, 2008)
Zilpaterol-HCl (Zilmax) is a β2-adrenergic receptor agonist approved as a growth promotant in feedlot cattle for use during the last 20 to 40 days prior to harvest. It is orally active and improves performance and total body lean tissue. The recommended dosage is 7.6 grams per ton of feed on a 100% dry matter basis. Steroidal implants are used in feedlot animals to improve average daily gain, feed efficiency, and total lean tissue deposition. Little is known about how Zilmax and steroidal implants influence growth performance when used in combination. Our objective was to evaluate performance of steers administered Zilmax in combination with the steroidal implant, Revalor1-S.
Keywords: Cattlemen' s Day; 2008; Kansas Agricultural Experiment Station contribution; no. 08-212-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 995; Beef; Cattle; Zilmax; Steroidal implants; Revalor-S.